Financial Sector Assessment Program : Malaysia - Basel Core Principles for Effective Banking Supervision - World Bank; International Monetary Fund (World Bank, Washington, DC, 2013)
Bank Negara Malaysia (BNM) employs a very well developed risk-focused regulatory and supervisory regime, consisting of a hands-on and comprehensive program of onsite supervision and extensive off-site macro, and micro, surveillance that is well integrated with its on-site supervision. This assessment of the current state of compliance with the Basel Core Principles (BCPs) in Malaysia has been undertaken as part of a joint International Monetary Fund (IMF)-World Bank Report on the Observance of Standards and Codes (ROSC) mission. The assessment was conducted from 4 April till 20 April 2012. It reflects the banking supervision practices of the BNM as of the end of March 2012 for the supervision of commercial banks. The assessment is based on several sources: (i) a detailed and comprehensive self-assessment prepared by the BNM ; (ii) detailed interviews with the BNM staff; (iii) review of laws, regulations, and other documentation on the supervisory framework and on the structure and development of the Malaysia financial sector; and (iv) meetings with individual banks, the banking association and an external auditor.